YouTube vlogging as access to possibilities a phenomenological study of an OG Filipino vlogger - De Vera, Marlon Jesspher B.; Saludadez, Jean A. (2021)
Access online through this link: https://www.plarideljournal.org/article/youtube-vlogging-as-access-to-possibilities-a-phenomenological-study-of-an-og-filipino-vlogger
Keywords: Popular culture; YouTube (Web resource); Video blogs; Cong TV